Refractory Intracranial Hypertension Due to Fentanyl Administration Following Closed Head Injury - Hocker, Sara E.; Fogelson, Jeremy L.; Rabinstein, Alejandro (Frontiers in Neurology, 2013)
Background Although the effects of opioids on intracranial pressure have long been a subject of controversy, they are frequently administered to patients with severe head trauma. We present a patient with an uncommon paradoxical response to opioids. Case Report A patient with refractory intracranial hypertension after closed head injury was managed with standard medical therapy with only transient decreases in the intracranial pressure. Only after discontinuation of opiates did the intracranial pressure become manageable without metabolic suppression and rescue osmotic therapy, implicating opiates as the etiology of refractory intracranial hypertension in this patient. Conclusions Clinicians should consider opioids as a contributing factor in malignant intracranial hypertension when findings on neuroimaging do not explain persistent and refractory intracranial hypertension.